Nástin nového rámce bezpečnostních studií (Czech Journal of International Relations, 2001)
Barry Buzan, Ole Waever , Jaap de Wilde: Security. A New Framework for Analysis. 1st ed. Boulder: Lyne Rienner Publishers, 1998, 237 stran, ISBN 1-55587-784-2.